PENGARUH KETERAMPILAN MANAJEMEN, MOTIVASI KERJA DAN KONFLIK PERAN GANDA TERHADAP KINERJA UMKM PEREMPUAN DI KOTA MANADO - Ambat, Yesika Tabita; Olivia S. Nelwan; Arrazi Bin Hasan Jan (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
Women's resilience in managing businesses offers enormous potential to accelerate national economic recovery. Increasing the number of women-managed MSMEs can absorb labor and reduce unemployment. However, women-owned businesses still struggle to grow. The majority of women-owned businesses are micro and small businesses. This is because women entrepreneurs still face various obstacles in running their businesses. It is crucial to understand the factors and characteristics that contribute to women's success in entrepreneurship in order to create a supportive environment for growth and unlock their full potential in entrepreneurship. This research was conducted on female MSMEs in Manado City. The research sample was 100 people obtained using accidental sampling technique. The results of the study show that: (1) at all age levels, the most common business sector is selling food/drinks; (2) Unmarried female MSMEs prefer to sell food/drinks, online buying and selling, and beauty salon businesses.